Dizziness handicap inventory - em um grupo de pacientes submetidos a reabilitação vestibular personalizada - Romero, Ana Carla Leite; Hayashi, Matheus Siqueira Yoshihiro; Kishi, Marcos Seizo; Cardoso, Ana Claúdia Vieira; Frizzo, Ana Cláudia Figueiredo (ABRAMO Associação Brasileira de Motricidade Orofacial, 2015)
PURPOSE: to describe the results obtained from the application of the DHI, pre and post customized vestibular rehabilitation in order to verify the efficiency of rehabilitation in this population. METHODS: the sample consisted of 10 patients with symptoms caused by disorders of the vestibular system and diagnosis of chronic vestibular dysfunction. These patients were evaluated for physical, emotional and functional aspects using the Dizziness Handicap Inventory pre and post customized vestibular rehabilitation. RESULTS: on the pre Dizziness Handicap Inventory it was verified that the physical aspects was the most highly scored, followed by the emotional and functional. Vestibular rehabilitation was effective, since there was a decrease in complaints concerning quality of life and better results in all the aspects evaluated in Dizziness Handicap Inventory post rehabilitation, only one patient reported improvement in emotional and functional, and worsening of the physical aspects. CONCLUSION: The Dizziness Handicap Inventory, Brazilian version, applied pre and post customized vestibular rehabilitation proved to be an efficient test to monitor patients undergoing vestibular rehabilitation, this device was able to show significant improvement in symptoms of chronic vertigo, and improved the quality of life of the patients in this study.

OBJETIVO: investigar o impacto da Reabilitação Vestibular personalizada e comparar os aspectos físicos, emocionais e funcionais pré e pós a aplicação do Dizziness Handicap Inventory. MÉTODOS: participaram 10 pacientes, com sintomas decorrentes de distúrbios do sistema vestibular e hipótese diagnóstica de disfunção vestibular crônica. Estes foram avaliados quanto aos aspectos físicos, emocionais e funcionais por meio do Dizziness Handicap Inventory pré e pós reabilitação vestibular personalizada. RESULTADOS: no Dizziness Handicap Inventory pré foi verificado que o aspecto físico foi o mais pontuado, seguido pelo emocional e funcional. A reabilitação vestibular foi eficaz, uma vez que houve diminuição nas queixas de qualidade de vida, e melhores resultados em todos os aspectos avaliados no Dizziness Handicap Inventory pós, apenas um paciente obteve melhora somente dos aspectos emocionais e funcionais, além de piora dos aspectos físicos. CONCLUSÃO: o Dizziness Handicap Inventory brasileiro aplicado pré e pós reabilitação vestibular personalizada mostrou-se como um teste eficaz para acompanhar pacientes submetidos a reabilitação vestibular, capaz de mostrar a melhora significante nos sintomas da vertigem crônica, além do impacto negativo na qualidade de vida dos pacientes deste estudo.
Dizziness handicap inventory- in a group of patients undergoing customized vestibular rehabilitation
Keywords: Vestibule, Labyrinth; Questionnaires; Rehabilitation; Vertigo; Vestíbulo do Labirinto; Questionários; Reabilitação; Vertigem